(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the main challenges in teaching mathematics and computer science in general education schools. Students’ low performance, methodological and pedagogical difficulties, as well as the insufficient infrastructure and resources of schools are examined. Scientifically-based solutions are proposed, including problem-based learning, project-based methods, gamification, visualization, and continuous professional development for teachers. The research results contribute to the development of students’ logical and analytical thinking skills, enhance the interactivity and effectiveness of lessons, and improve performance in national and international assessments.